우리나라와 신남방 국가의 농산물 수출결정요인 분석 - 박현희(Hyun-Hee Park), 조성제(Sung-Je Cho) (무역연구, 2020)
Purpose The purpose of this study is to identify factors that significantly affect export decisions in the agricultural sector, including the entire export sector with Korea and the New Southern Countries(ASEAN Countries and India), and derive insights and implications for expanding exports. Design/Methodology/Approach This study analyzes panel data using gravitational models on the overall export and agricultural export scales for the period covering 1998 through 2018 between Korea and the New Southern countries. Findings In the overall export sector between Korea and the New Southern countries, GDP per capita, economic growth rate (GROW), population (POP) and FTA (FTA) have been shown to have a significant impact on export decisions. In the agricultural export sector, the consumer price index (CPI) and the relative price index (REPRI) were analyzed to have a statistically significant impact, and in particular, the FTA conclusion (FTA) had a positive impact on exports. Research Implications In the field of agricultural exports, it is believed that the discovery of export determinants to expand agricultural trade with the new southern countries could provide implications for expanding Korea’s agricultural export market in the future. According to the analysis results, the Consumer Price Index (CPI), the Relative Price Index (REPRI), and the FTA (FTA) variables are important factors in determining exports. In particular, the government should make efforts to improve the system and procedures for implementing the FTA agreement, considering that the FTA has a significant impact on the agricultural export market. KCI Citation Count: 10